2009
DOI: 10.1073/pnas.0908039106
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the Cdc45-Mcm2–7-GINS complex in human cells requires the Ctf4/And-1, RecQL4, and Mcm10 proteins

Abstract: In eukaryotes, the activation of the prereplicative complex and assembly of an active DNA unwinding complex are critical but poorly understood steps required for the initiation of DNA replication. In this report, we have used bimolecular fluorescence complementation assays in HeLa cells to examine the interactions between Cdc45, Mcm2-7, and the GINS complex (collectively called the CMG complex), which seem to play a key role in the formation and progression of replication forks. Interactions between the CMG co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
145
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(159 citation statements)
references
References 34 publications
12
145
2
Order By: Relevance
“…Moreover, the association of RecQ4 with chromatin and the association between TopBP1 and the RecQ4 amino-terminal domain do not require CDK (Sangrithi et al 2005;Matsuno et al 2006). Furthermore, the formation of the CMG complex in HeLa cells requires RecQ4 and Mcm10 (Im et al 2009), and RecQ4 expressed in human 293 cells binds to Mcm10 and associates with the CMG complex in an Mcm10-dependent manner (Xu et al 2009). These results suggest that RecQ4 functions later in the initiation step compared with Sld2.…”
Section: Recq4mentioning
confidence: 99%
“…Moreover, the association of RecQ4 with chromatin and the association between TopBP1 and the RecQ4 amino-terminal domain do not require CDK (Sangrithi et al 2005;Matsuno et al 2006). Furthermore, the formation of the CMG complex in HeLa cells requires RecQ4 and Mcm10 (Im et al 2009), and RecQ4 expressed in human 293 cells binds to Mcm10 and associates with the CMG complex in an Mcm10-dependent manner (Xu et al 2009). These results suggest that RecQ4 functions later in the initiation step compared with Sld2.…”
Section: Recq4mentioning
confidence: 99%
“…Interactions between TopBP1-interacting, replication-stimulating protein (Treslin) (homolog of Sld3) and MDM two binding protein (MTBP) (homolog of Sld7) with topoisomerase-IIbeta-binding protein 1 (TopBP1) (homolog of Dpb11) have been detected in higher eukaryotes, suggesting that the mechanism used by yeast for the chromatin loading of Cdc45 and GINS may be conserved (8). However, in vivo studies in HeLa cells using bimolecular fluorescence complementation assays reported that Mcm10 as well as RecQ protein-like 4 (RecQL4) (homolog of Sld2) and Ctf4 are required for human CMG (hCMG) complex formation (9).…”
mentioning
confidence: 99%
“…Previous studies by others and us showed that the acidic nucleoplasmic DNA-binding protein 1 (And-1) is a replisome component and is required for efficient DNA replication in unperturbed cells (Zhu et al, 2007;Errico et al, 2009;Gambus et al, 2009;Im et al, 2009;Yoshizawa-Sugata & Masai, 2009;Bermudez et al, 2010;Li et al, 2012b). Ctf4/Mcl1, the ortholog of And-1 in yeast, is required for chromosome transmission fidelity, sister chromatin cohesion, DNA damage repair, maintenance of genome integrity, and the regulation of telomere replication (Kouprina et al, 1992;Hanna et al, 2001;Williams & McIntosh, 2002;Mayer et al, 2004;Tsutsui et al, 2005).…”
Section: Introductionmentioning
confidence: 99%